Animal growth models as a tool to estimate resilience indicators in Bos indicus and Bos taurus heifers: Selection effects and genetics parameters - Rodrigues, Gustavo Roberto Dias [UNESP]; Rezende, Vanessa Theodoro; Mercadante, Maria Eugênia Zerlotti [UNESP]; Bonilha, Sarah Figueiredo Martins; Canesin, Roberta Carrilho; Raineri, Camila; Valente, Júlia De Paula Soares [UNESP]; Ligori, Viviane Andrade [UNESP]; Gonçalves Cyrillo, Joslaine Noely Dos Santos (Elsevier, 2024)
The aim of the study is to analyze different growth models for the estimation of resilience indicators and to assess the impacts of selection for yearling weight and breed on the resilience capacity of Nelore, Guzerá and Caracu heifers. Weight records of females (n = 38,937) from birth to the measurement of weight adjusted to 550 days of age (W550) were used to fit growth curves. Next, three resilience indicators were calculated based on weight deviations (residuals): natural logarithm of residual variance (LnVar), lag-one autocorrelation (rauto), and skewness of deviations. The means of the resilience indicators were compared between Nelore selection lines (NeC: selected based on the mean of the contemporary groups for W550; NeS: selected based on the highest selection differential for W550; and NeT: selected based on an index considering highest selection differential for W550 and lower residual feed intake) and breeds (Nelore, Guzerá, and Caracu). Additionally, the heritabilities of the resilience indicators were estimated, as well as the genetic correlations between these indicators and productive traits using blupf90+ program. The results indicated that selection for yearling weight had an impact on the resilience capacity of the animals, with NeS and NeT heifers exhibiting greater weight variability (mean LnVar: 6.09 ± 0.02 and 6.12 ± 0.02, respectively) but also the highest recovery rate (rauto: 0.04 ± 0.01 and 0.04 ± 0.01, respectively). Nelore heifers were the most resilient, with a fast recovery rate (rauto: 0.01 ± 0.05) and there was little influence of the environment on performance (skewness: 0.00 ± 0.01). Caracu was the breed most affected by environmental disturbances (LnVar: 6.46 ± 0.02), with inverse subsequent weight deviations (rauto: -0.12 ± 0.05). The heritabilities of the resilience indicators were low and moderate, with the highest estimates being observed for LnVar in the three breeds (0.05 ± 0.05 to 0.38 ± 0.07). LnVar and skewness showed moderate positive genetic correlations with W550 (0.29 ± 0.18 to 0.55 ± 0.12), while the genetic correlations of rauto with W550 were weak and negative (-0.19 ± 0.17 to -0.28 ± 0.20). Selection for yearling weight influenced the resilience capability to environmental challenges in heifers during the growth phase. The results reinforce the greater adaptation capacity of zebuine breeds (Bos indicus) to tropical environments when compared to taurine breeds (Bos taurus). LnVar showed enough genetic variability to be included in breeding programs for zebu breeds aiming selection for more resilient animals.
Keywords: Nelore; Novel phenotypes; Residual variance; Weight deviations